Effects of Parallel Importation and Power Structures on Price Competition in Duopolistic Supply Chains. (26th March 2021) - Rong, Luqing; Xu, Maozeng; Chen, Xiaofeng; Lu, Zhiping
Abstract : Multinational manufacturers (MNMs) achieve significant gains from product quality and reputation in entering emerging markets while facing many operational risks, such as parallel importation (PI) and market power structures. This paper focuses on a duopolistic supply chain consisting of one MNM and one local manufacturer (LM) in an emerging market with low willingness-to-pay (WTP). Within the game analytical framework, we consider different market power structures and investigate the impact of PI on the manufacturers' price competition, and we further discuss the MNM's countermeasures in high and low WTP markets. We find that PI does not occur when the WTP ratio is below the threshold or the transaction cost is high. Power structures significantly affect the participant's profitability, the LM's gains are maximized if the MNM fully dominates the market, and the MNM loses the minimum if the LM exclusively rules the market. When in codominant structure, the parallel importer achieves maximum gains while the MNM's profits rise in the market WTP ratio interval. PI activities boost the benefits for the LM and the parallel importer, whereas increasing transaction costs diminish those effects and promote the MNM's profitability. PI promotes or deters price competition in duopolistic supply chains depending on power structures. In addition, increasing either the level of product substitution or quality perception restrains PI and improves the LM's earnings, but the latter expands the MNM's losses.